2017
DOI: 10.1080/1331677x.2017.1392882
|View full text |Cite
|
Sign up to set email alerts
|

Do house prices influence stock prices? Empirical investigation from the panel of selected European Union countries

Abstract: This study examines the long-run and causal relationship between house prices and stock prices in the panel of 22 European Union (EU) countries, covering the monthly data from January 2007 to October 2012. The results show that house prices and stock prices variables are stationary at their first difference, and Pedroni's heterogeneous cointegration test does not confirmed the long-run relationship between the two variables; hence, it is imperative to employed dynamic OLS estimator for robust statistical infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Our approach rests on the large impact of house prices on the business cycle (Leamer, 2015) and on waves of optimism and pessimism in the economy (Chahrour & Gaballo, 2021). Such a significant impact of housing on the economy can affect stock prices (Hong & Li, 2020;Bahmani-Oskooee & Ghodsi, 2018;Ali & Zaman, 2017). Indeed, the links between different macroeconomic variables may become stronger during booming house prices (Ryczkowski, 2019;Goodhart & Hofmann, 2008).…”
Section: The Mechanismmentioning
confidence: 99%
“…Our approach rests on the large impact of house prices on the business cycle (Leamer, 2015) and on waves of optimism and pessimism in the economy (Chahrour & Gaballo, 2021). Such a significant impact of housing on the economy can affect stock prices (Hong & Li, 2020;Bahmani-Oskooee & Ghodsi, 2018;Ali & Zaman, 2017). Indeed, the links between different macroeconomic variables may become stronger during booming house prices (Ryczkowski, 2019;Goodhart & Hofmann, 2008).…”
Section: The Mechanismmentioning
confidence: 99%
“…Yang and Turner (2016) explored the impact of macroeconomic shocks on housing price dynamics for Sweden and concluded that there is a long-run temporal diffusion of shocks between the region. Based on a panel set of observations for 22 countries in the European Union with monthly observations covering the period from 2007 to 2012, Ali and Zaman (2017) investigated the causal association between stock prices and housing prices. Among the countries, a negative causal association between stock prices and housing prices was revealed for five countries.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In China, many authors have studied the house price index, for example: Ding et al (2014), Shen et al (2016), Shi et al (2017) and Jiang et al (2018). In addition, several studies have analyzed house price index with data from many countries, for example: Arestis and Gonzalez (2014), Hui and Chan (2014), Lin and Fuerst (2014), Liow and Schindler (2014), Ali and Zaman (2017), Lim (2018). Motivated by this gap, the author expects this study can contribute to the current literature by establishing determinants of apartment prices in Ho Chi Minh city.…”
Section: Introductionmentioning
confidence: 97%